2015
DOI: 10.1186/s12879-015-0920-1
|View full text |Cite
|
Sign up to set email alerts
|

A matched cross-sectional study of the association between circulating tissue factor activity, immune activation and advanced liver fibrosis in hepatitis C infection

Abstract: BackgroundTissue factor (TF) is a protein that mediates the initiation of the coagulation cascade. TF expression is increased in patients with poorly-controlled HIV, and may be associated with increased immune activation that leads to cardiovascular morbidity. The role of TF in immune activation in liver disease in hepatitis C virus (HCV)-monoinfection and HIV/HCV-coinfection has not been explored.MethodsFifty-nine patients were stratified: A) HIV-monoinfection (N = 15), B) HCV-monoinfection with chronic hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
(37 reference statements)
0
13
0
3
Order By: Relevance
“…Previous literatures have suggested higher thrombin level and elevated tissue factor level are associated with advanced hepatic fibrosis. 37 , 38 Therefore, one could expect that HCV patients with chronic active hepatitis who require treatment may have higher risk of VTE. Second, previous literatures have reported microvascular thrombosis as a rare complication of interferon treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literatures have suggested higher thrombin level and elevated tissue factor level are associated with advanced hepatic fibrosis. 37 , 38 Therefore, one could expect that HCV patients with chronic active hepatitis who require treatment may have higher risk of VTE. Second, previous literatures have reported microvascular thrombosis as a rare complication of interferon treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a cross-sectional study from the MACS cohort that found HCV/HIV co-infection to be an independent risk factor for subclinical atherosclerosis assessed by non-contrast CT and CT angiography [85]. A small study reported evidence of higher tissue factor activity (measured as microparticles tissue factor), a procoagulant factor, and associated CD4 T cell activation in HCV patients both mono- and HIV-coinfected suggesting a potential mechanism of immune activation and coagulopathy that may predispose to cardiovascular disease [86]. In another prospective study, immune activation markers were compared between HIV monoinfecetd and HIV/HCV coinfected (with and without cirrhosis) ART treated patients with suppressed plasma HIV viremia during 12 months [87].…”
Section: Cryptococcusmentioning
confidence: 99%
“…The lack of a correlation between grade of liver fibrosis and plasma asTF levels may be owing to a contribution to the formation of microthrombi in hepatic sinusoids promoting liver disease progression rather than a direct involvement of asTF in the fibrogenic process. Interestingly, it has been reported that the amount of TF was higher in patients with HIV, HCV, and HIV/HCV coinfection with advanced fibrosis than those with low fibrosis [29]. Indeed, Villa et al [30] reported previously that an anticoagulant treatment with enoxaparin, which acts on microthrombosis, improves liver function and Child-Pugh score, thus decreasing the progression of liver disease.…”
Section: Discussionmentioning
confidence: 99%